2017
DOI: 10.1002/hipo.22755
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids prevent the differential long‐term effects of exposure to severe stress on hippocampal‐ and amygdala‐dependent memory and plasticity

Abstract: Exposure to excessive or uncontrolled stress is a major factor associated with various diseases including posttraumatic stress disorder (PTSD). The consequences of exposure to trauma are affected not only by aspects of the event itself, but also by the frequency and severity of trauma reminders. It was suggested that in PTSD, hippocampal-dependent memory is compromised while amygdala-dependent memory is strengthened. Several lines of evidence support the role of the endocannabinoid (eCB) system as a modulator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 117 publications
(183 reference statements)
3
19
0
Order By: Relevance
“…and the fatty acid amide hydrolase (FAAH) inhibitor URB597 (0.3 mg/kg, i.p.) 2 h after shock exposure [6]. We found that cannabinoids administered in the aftermath of trauma can prevent the development of PTSD-like behaviors [2,7].…”
Section: Introductionmentioning
confidence: 75%
See 4 more Smart Citations
“…and the fatty acid amide hydrolase (FAAH) inhibitor URB597 (0.3 mg/kg, i.p.) 2 h after shock exposure [6]. We found that cannabinoids administered in the aftermath of trauma can prevent the development of PTSD-like behaviors [2,7].…”
Section: Introductionmentioning
confidence: 75%
“…Behavioral metaplasticity involves altered plasticity at the level of the neural systems following exposure to stress. We have shown that exposure to shock and reminders induced metaplasticity in the CA1 and BLA [6].…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations